2016
DOI: 10.1155/2016/3710312
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Postoperative Pain Trajectories following Total Knee Arthroplasty: A Longitudinal Study of Patients Admitted to a Russian Orthopaedic Clinic

Abstract: This study explores sociodemographic, clinical, and surgical factors in relation to pain trajectories during the first 3 days following total knee arthroplasty (TKA). 100 patients (mean age 63.5 ± 7.8 years and 93% female) consecutively admitted for uncomplicated primary TKA were prospectively included. Postoperative pain was assessed using pain diaries. Measures of preoperative pain, symptoms, daily functioning, quality of life, comorbidities, knee function, perioperative characteristics, and physical/biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 52 publications
0
46
0
2
Order By: Relevance
“…Pain intensity after knee surgery may be influenced by preoperative pain intensity. 14 The patient population in our study was generally healthy and reported low preoperative pain intensity. Pain responders experienced slightly higher preoperative pain intensity than nonresponders.…”
Section: Discussionmentioning
confidence: 91%
“…Pain intensity after knee surgery may be influenced by preoperative pain intensity. 14 The patient population in our study was generally healthy and reported low preoperative pain intensity. Pain responders experienced slightly higher preoperative pain intensity than nonresponders.…”
Section: Discussionmentioning
confidence: 91%
“…Following this initial review, 46 full-texts were assessed for eligibility of which 20 manuscripts were excluded for at least one of the following reasons: non-significant findings (n = 6) 1,10,48,56,58,63 , the analyses/results were not relevant to review hypotheses (n = 6) 6,9,20,35,42,90 , and the critical test statistic was not reported, could not be computed based on reported data, and could not be obtained after contact with the author (n = 3) 3,18,86 (see Figure 1). The latter criterion included studies reporting pvalue ranges (e.g.…”
Section: Study Selection and Search Criteriamentioning
confidence: 99%
“…Page et al showed that patients with high pain trajectory after knee replacement had more severe preoperative pain, more preoperative functional impact, and more psychological distress. 24 Kornilov et al 15 showed that high pain trajectory were significantly related to preoperative anxiety. The preoperative morphine consumption has also been linked to a higher intensity of postoperative pain 11 and to a more gentle slope of pain resolution after major surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…The median pain intensity score in the postoperative acute care unit was 4 (0-7), the median morphine titration doses were 6 mg (0-7) and cumulative consumption over the first 48 hours after surgery was 11 mg (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Sixteen patients (34%) had a high pain trajectory.…”
Section: Acute Pain Trajectorymentioning
confidence: 99%